Stitch draw - James, Rosie (Batsford, 2014)
When you want to make a fresh artistic statement, put down the pencil and turn on the sewing machine instead! Figurative stitch work is a hot new look, and Rosie James--a leading exponent of the style--takes newcomers by the hand and guides them through its ins and outs. Using her own gorgeous drawings, plus those of other top artists, she lays out a repertoire of techniques, including transferring drawing to cloth, stitching on photographs, using multicolored threads, layering images, and creating a pleasing composition.